A multicentre confirmatory single‐arm trial of the safety and efficacy of a transanal drain for prevention of anastomotic leakage after surgery for rectal cancer. (18th August 2021) - Nishizawa, Yuji; Nishigori, Hideaki; Tsukada, Yuichiro; Sasaki, Takeshi; Tsukamoto, Shunsuke; Kanemitsu, Yukihide; Nakano, Daisuke; Yamaguchi, Tatsuro; Otsuka, Koki; Nakamura, Takatoshi; Shiomi, Akio; Iwasaki, Natsuko; et al.
Abstract: Aim: Recent reports have described the use and efficacy of several types of transanal tube (TAT) for preventing anastomotic leakage by reducing intraluminal pressure. The aim of this study was to evaluate the safety and efficacy of a newly developed TAT for the prevention of anastomotic leakage after low anterior resection (LAR) for rectal cancer. Method: A multicentre confirmatory single‐arm trial was designed to evaluate the safety and efficacy of a new TAT after LAR for rectal cancer. A total of 115 patients were registered in the trial at several cancer centres and other hospitals. All patients initially received reconstruction with a stapled anastomosis, but 18 then underwent creation of a diverting stoma. Of the remaining 97 patients, the first 96 were included in the protocol‐defined primary analysis set. The primary outcome was the incidence of symptomatic leakage and the secondary endpoint was the incidence of complications associated with use of the TAT. The TAT was placed during LAR without creating a covering stoma and the drain was removed 4 or 5 days postoperatively. Results: The rate of symptomatic leakage was 5.2% (95% confidence interval 1.7–11.7), which was significantly lower than the predetermined threshold value of 15.8% (one‐sided p ‐value 0.0013). Only one patient had Grade 3 rectal bleeding that might have been related to use of the TAT. Conclusion: This nonrandomized study shows that the TAT appears to be safe and results in lower rates of anastomotic leakage in LAR compared with previous studies.